A escolarização de pessoas trans e travestis em Sobral-CE: uma análise dos relatos de experiência - Santiago, Vanessa Cunha (2022)
The present research aims to put on evidence the schooling of trans people in Sobral-CE. The idea for this research emerged gradually and was structured from the Travessias study group, organized by extension students from the Laboratory of Practices and Research in Psychology and Education (LAPPSIE) at the Federal University of Ceará, Sobral campus. The research problem established here comes from the intersection between the LGBT population – more specifically the trans and travesti population – and education in Sobral. In addition to discussing quantitative data on this population inside and outside school, the proposal is to deal with the experience of these people in Sobral schooling. To do so, we start with the following question: how is the schooling experience of trans and travestis in Sobral education? In order to achieve the intended objectives of this research, which is of a qualitative nature, we held workshops at the Estação da Juventude in Sumaré, Sobral. For the interpretation of the collected data, we used the Content Analysis tool, which allowed us to list three categories of analysis: “the dimension of difference and recognition”; “in the walls of the school” and “beyond the walls of the school”. Each of these categories condenses topics addressed in the workshops, from institutional to personal relationships, the relationship with the school environment and its surroundings, reactions to the violence suffered. As a theoretical support for the elaboration of the research results, we have Judith Butler, Guacira Lopes Louro, Berenice Bento, bell hooks, Djamila Ribeiro, Inés Dussel, among others. As a technical product of the workshops, we produced, in co-authorship with the participants, a material called Zine Trans-formador, which points out some ways of dealing with transphobia in the school environment.